Christian den Fjerdes foliobibel og dens ikonografi - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 1990)
During the reign of Christian IV, King of Denmark 1588-1648, three Bibles were published: 1) a translation from the original languages by H.P. Resen 1607; 2) a revised edition of 1), made by Hans Svane 1647; 3) a Church Bible in folio: the third and last of the Danish Luther Bibles, printed 1633 in Copenhagen. The great Luther Bible was furnished with the same woodcuts by Virgilio Solis as was Fredcerik Il’s Bible of 1589. In addition, however, it was provided with new title copers for the Law, the Prophets, and the New Testament respectively. The first title-page, which serves as frontispiece for the Bible as a whole as well as for the Pentateuch and the historical books, is of a special interst iconographically. It was commissioned by the faculty of theology and the Chancellor of the University of Copenhagen in a period, when one of the most influential theological professors was Jesper Brochmand who -in his principal dogmatic work »Universae theologiae systema« (1633) - provided a set of arguments for the form of »theocracy« prevalent in Denmark before the establishment of ab solute monarchy in 1660. Brochmand’s concept of a »mixed monarchy« -the combined authority of King and Council - seems to be alluded to in the relation between the figurs of the title-page. In the lower part of the page Kings David and Josiah are represented together with the prophete Samuel. An examination of the regalia which the kings hold in their hands makes clear that they are the regalia of the Danish realm. Furthermore, an investigation of political writings and funeral orations gives as a result that Christian IV and his son (who the name of Christian V) were identified with Kings David and Josiah respectively. These Kings derive power from God, but according to Brochmand’s system they receive it through mediators who also are entrusted with the task of electing the King and making sure that he fulfill his duties to his people and to the Church. In a Scriptural context this mediator is Samuel - and in the contemporary political context he is the Bishop of Zealand, the highest divine in the realm and member of the Council. Behind the figure of Samuel the Council’s representative thus can be said to stand hiddne, occopying the position of the King’s »ordinator« which fell to the lot of none other than Jesper Brochmand himself at the coronation of Frederik III, Christian IV’s successor, in 1648. The title-page, it follows, is a political one. It had to be altered when it was put to use in Queen Christina’s Finnish Bible of 1642. The title’s motive with the Old Testament kings is used as a decorative painting in Jerlev church near vejle, and on a tombstone from Viborg, but here the political allusions are absent.